Pembelajaran Ekstrakurikuler Pada Lagu Sinaran di SMK Negeri 7 Palembang - Setia Berta Sastra Hedi; Irfan Kurniawan; Silo Siswanto (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
Based on the above background, the formulation of the problem in the study is "How is the Implementation of Extracurricular Learning in Sinaran Songs at SMK Negeri 7 Palembang" This study uses a descriptive method with a qualitative approach to examine how extracurricular learning of "sinaran" songs at SMK Negeri 7 Palembang takes place based on its quality. In line with the chosen approach, the method used in this study is a descriptive method. This method is used to recognize and describe the actual state of the research object in accordance with the findings during the research in the field, regarding extracurricular learning of the song "sinaran" at SMK Negeri 7 Palembang.From the discussion above, it can be said that the teaching method used by the trainer in this extracurricular activity is successful. Students who were initially not skilled in playing musical instruments have made significant progress. Previously, they lacked confidence when performing in public, but now they are showing an increase in confidence. Researchers concluded that coaches not only focus on skill development, but also on strengthening students' mentality to be more confident when performing. The conclusion that the researcher can describe in this discussion is that the method applied by the trainer has advantages and disadvantages. The advantages of the peer tutor method applied by the trainer can make students more comfortable in interacting because it creates a learning atmosphere that tends to be relaxed, can increase confidence, reduce pressure or be less afraid to make mistakes in acting or asking questions.